Ultrastructural and immunocytochemical studies on the olfactory receptor neurons in the Ichthyosaura alpestris. (1st September 2020) - Różański, Józef J.; Capillo, Gioele; Lauriano, Eugenia R.; Aragona, Marialuisa; Kuciel, Michał; Zaccone, Giacomo; Żuwała, Krystyna D.
Abstract: Morphological and immunohistochemical studies were conducted on the alpine newt Ichthyosaura alpestris, which is representative of the family Salamandridae. The aim of the study was to determine the differences in olfactory organs structural properties, especially in the olfactory epithelium (OE) of the main olfactory chamber (MOC) and the vomeronasal organ (VNO) between breeding and non‐breeding seasons in this species. A change in environments occurs for alpine newts in the course of the annual cycle because of its aquatic adaptations for reproduction. The results confirmed the variability in the shape and size of olfactory organs between breeding and non‐breeding seasons. The presence of the ovoid cells with microvilli at its apical part was determined in the OE of males and females during breeding season. Giant ORNs, a subtype of ciliated ORNs, were observed only during the newt's non‐breeding season. The presence of the ovoid cells during the terrestrial phase was not determined. Thus, its role might be associated with reproduction.